On the Harmonic Problem with Nonlinear Boundary Integral Conditions. (23rd February 2014) - Hacene, Saker
Abstract : In the present work, we deal with the harmonic problems in a bounded domain ofℝ 2 with the nonlinear boundary integral conditions. After applying the Boundary integral method, a nonlinear boundary integral equation is obtained; the existence and uniqueness of the solution will be a consequence of applying theory of monotone operators.